Native Oils from Apple, Blackcurrant, Raspberry, and Strawberry Seeds as a Source of Polyenoic Fatty Acids, Tocochromanols, and Phytosterols: A Health Implication - Marek Pieszka; Władysław Migdał; Robert Gąsior; Magdalena Rudzińska; Dorota Bederska-Łojewska; Magdalena Pieszka; Paulina Szczurek (Journal of Chemistry)
The oils from strawberry, blackcurrant, raspberry, and apple seeds were characterized by a high content of unsaturated fatty acids (90.8%, 88.6%, 94.0%, and 86.9%, resp.). Strawberry and raspberry oils had high levels of C18:2 (45.4% and 49.0%) and αC18:3 (29.0% and 33.0%, resp.). Blackcurrant oil was the richest source of γC18:3 (18.5%) and C18:4 (3.6%). Apple oil had high levels of C18:2 (55.5%) and C18:1 (29.4%). Blackcurrant oil had 229.5 mg/100 g of tocochromanols, predominantly γ-tocopherol (117.8 mg/100 g) and α-tocopherol (84.3 mg/100 g). Raspberry oil was rich in γ-, α-, and δ-tocopherol (193.5; 65.6; and 32.2 mg/100 g, resp.). Strawberry oil contained γ- and δ-tocopherol, 49.0 and 6.1 mg/100 g, respectively. Apple contained all isomers of α-, β-, γ-, and δ-tocopherols at 41.7, 62.7, 13.6, and 21.8 mg/100 g, respectively. The level of tocotrienols in the analysed oils ranged from 0.85 to 6.73 mg/100 g. Ten different phytosterols were found in the tested oils. The richest sources of phytosterols were blackcurrant oil (6824.9 μg/g) followed by raspberry (5384.1 μg/g), strawberry (4643.1 μg/g), and apple oil (3460.0 μg/g). The dominant compound in the analysed oils was sitosterol, from 2630 μg/g in apple oil to 3630 μg/g in blackcurrant oil.